Diplomasi Perdamaian Dunia Melalui Perempuan Penjaga Perdamaian Dunia Pada Pemerintahan Presiden Joko Widodo - Pratama, Dafa Wisuda; Argenti, Gili; Marsingga, Prilla (Peneliti.net, 2024)
Indonesia is being hit by a declining economic situation due to the Covid-19 virus. This certainly affects the views of other countries on diplomatic relations and the image of Indonesia. To overcome Indonesia's bad image, Indonesia sent as many as 570 female personnel to various United Nations peacekeeping missions. In writing this journal is to use qualitative methods, use data collection techniques that use literature studies, collecting information from various reference sources, and using the type of data in this writing using secondary. There are five discussions in this article, namely, the History of the Establishment of the United Nations and Efforts to Maintain World Peace, Diplomacy Conducted by Indonesia at the United Nations in Maintaining World Peace, Restoring Indonesia's Image Through Peace Missions, Indonesia Creating a Resolution for Women's World Peacekeepers, Promotion of Peace by Establishing Civil-Military Relations in Lebanon through the Role of Women in the Indonesian Armed Forces and Gender Equality in Maintaining World Peace.